My iz Kronshtadta - Dzigan, Efim (Soviet Union : Mosfilm, 1936)
The Soviet official version of the Kronstadt mutiny. The main protagonist is a Red seamen who helped to defend the road to Petrograd against the White Guards commanded by General Yudenitch. He belongs to the fleet stationed at Kronstadt at the Baltic Sea base. At first he is fanned to flame by the word and example of the veteran commissar who has come to the naval base to recruit his Petrograd defense corps. It is not until after his comrades are driven by the White soldiers to the top of a cliff and forced to jump into the sea, with their hands tied behind their backs and rocks strapped to their chests, that the sailor awakens to his party responsibility. At the end of the film, as he leads the Kronstadt marines to force 'the Whites' off the same cliff he, glaring defiantly, growls "And who else wants Petrograd?"
Duration: 01:28:00
Keywords: Fiction films